TARAS SHEVCHENKO AND GALICIA (XIX - EARLY XX CENTURIES) - Райківський, І. Я. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article highlights the influence of T. Shevchenko’s works on modern Ukrainian national identity formation in Galicia from the 1840s to the early XX century. A special focus is on the Russian Trinity’s first impression of the prominent Ukrainian writer and national ideologist, as well as on T. Shevchenko’s interest in Galicia and the formation of the Shevchenko cult in the region. Additionally, the author comments on the availability of the first 1840 edition of “Kobzar” to Galician public figures.